Effect of Model Problem Solving on Student’s Problem Solving Skills In Climate Change Material Class VII SMPN 34 Padang - Rika Gustia; Ristiono Ristiono; Zulyusri Zulyusri; Heffi Alberida (Universitas Negeri Padang, 2019)
This research is motivated by the problem of the low skills of problem solving students. In the learning process the teacher rarely trains students problem solving skills and currently Science literacy in Indonesia is low compared to other countries. The results of the preliminary test showed that the average problem solving skills of students was less than 50%. This study aims to look at the effect of the problem solving model on problem solving skills of grade VII students of SMPN 34 Padang. This type of research is a quasi-experimental design with the Control Group Posttest Only Design. The study population was VII grade students of 34 SMPN Padang in the 2018/2019 academic year. The research sample of students in class VII 4 as the experimental class and VII 5 as the control class. Sampling using a porposive sampling technique. Instruments in the form of observation sheets observation of student activities to obtain data problem solving skills, observation sheets to obtain scientific attitude data, question sheets to obtain knowledge data. Based on the results of the students' knowledge competency research, the tcount 2,24> ttable 1,67. The activity of problem solving skills of students in the experimental class is higher than the control class. The conclusion of the study is that the application of the problem solving model has a positive effect on problem solving skills of grade VII students of SMPN 34 Padang.